Brain processing of pain in patients with unresponsive wakefulness syndrome. Issue 2 (28th January 2013) - Markl, Alexandra; Yu, Tao; Vogel, Dominik; Müller, Friedemann; Kotchoubey, Boris; Lang, Simone
Abstract By definition, patients with unresponsive wakefulness syndrome (UWS) do not experience pain, but it is still not completely understood how far their brain can process noxious stimuli. The few positron emission tomography studies that have examined pain processing did not yield a clear and consistent result. We performed an functional magnetic resonance imaging scan in 30 UWS patients of nontraumatic etiology and 15 age‐ and sex‐matched healthy control participants (HC). In a block design, noxious electrical stimuli were presented at the patients' left index finger, alternating with a resting baseline condition. Sixteen of the UWS patients (53%) showed neural activation in at least one subsystem of the pain‐processing network. More specifically, 15 UWS patients (50%) showed responses in the sensory‐discriminative pain network, 30% in the affective pain network. The data indicate that some patients completely fulfilling the clinical UWS criteria have the neural substrates of noxious stimulation processing, which resemble that in control individuals. We therefore suppose that at least some of these patients can experience pain.